The Effect of Special Exercises Using Training Tools On the Development of Some Fundamental Skills for Youth Soccer Players Aged (15-17) years - frhan, Ahmed; Anwar, Saif (Journal of Physical Education, 2018)
The Effect of Special Exercises Using Training Tools On the Development of Some Fundamental Skills for Youth Soccer Players Aged (15-17) yearsThe research aimed at designing special exercises using training tools intended to develop the basic skills of soccer; passing and scoring, in order to better investment opportunities possible during matches and thus record number of more goals. The problem of the study lies in the weakness of some basic skills in youth players aged (15-17 years). The researcher used the experimental method. The subjects were (20) players from Alshurta Youth football Club. They were divided into two equal experimental and control groups. The researcher concluded that the special exercise using training tools has led to the development of specific skills games understudy. Finally the researcher recommended using these exercises during training on these skills for their importance in achieving good results in matches.